Papers of Barry James Maddern - Maddern, B. J. (Barry James), 1937-1994.; Australian Industrial Relations Commission; Australian Conciliation and Arbitration Commission (1958)
The collection comprises speeches and addresses given by Barry Maddern from 1970-1980, personal cuttings files from 1967-1994, and his personal collection of industrial relations cartoons from 1970-1981. There is also a folder of letters of congratulations (and replies) on the various appointments in his work in industrial relations and a small collection of photographs and documents which record milestones in his life and career. A small collection of reports and papers from a visit to Papua New Guinea in 1963 under the auspices of Rotary and copies of magazines edited by Maddern document the beginnings of his career.
Manuscript reference no.: MS 9004.
Judge. Maddern's career began as an industrial advocate in the oil refining industry. He studied law at the University of Melbourne, and in 1966 he was admitted to the Victorian Bar. From 1967 to 1980 Maddern was an industrial advocate, first as a barrister and later as an independent advocate for the National Employees Policy Committee and various employer organisations. He was Deputy-President of the Australian Conciliation and Arbitration Commission from 1980 to 1985, and President from 1985-1989. In 1989 he was appointed president of the Australian Industrial Relations Commission, a position he held until his death.
Descriptive list available (2 p.)
Keywords: Maddern, B. J. -- 1937-1994 -- Archives; Judges -- Australia -- Archives; Lawyers -- Australia -- Archives; Labor courts -- Australia; Arbitration, Industrial -- Australia; Judges; Lawyers